2001
DOI: 10.1080/146598901300271095
|View full text |Cite
|
Sign up to set email alerts
|

A review of GP records relating to methadone-associated deaths in the Lothian region of Scotland 1997-9

Abstract: Aims To ascertain the characteristics of patients whose death was associated with methadone intoxication during the period 1997-9 in the Lothian region of Scotland. Design Patients were identified from death certificates. General practitioner records relating to methadone-associate d deaths were reviewed in association with autopsy, toxicology and police reports. Deprivation categories (DepCat) were derived from the postal code of residence and the Carstairs index. Findings There were 77 methadoneassociated de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…At least three-fifths of deaths associated with methadone in England and Wales are accounted for by the use of methadone which may have been illicitly obtained (Ghodse et al, 2003). Rates as high as 75% have been reported in Scotland (Fiddler et al, 2001).…”
Section: Methadone Prescribing and Diversionmentioning
confidence: 98%
“…At least three-fifths of deaths associated with methadone in England and Wales are accounted for by the use of methadone which may have been illicitly obtained (Ghodse et al, 2003). Rates as high as 75% have been reported in Scotland (Fiddler et al, 2001).…”
Section: Methadone Prescribing and Diversionmentioning
confidence: 98%
“…The literature review resulted in 207 articles, with a final inclusion of 84 papers ( Table S1, Supplementary Electronic Material ) [ 16 , 19 , 20 , 29 , 34 , 35 , 36 , 37 , 38 , 39 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ,…”
Section: Resultsmentioning
confidence: 99%
“…In the majority of literature series and cases, BZDs were the most frequent co-consumed substance in addition to methadone [ 19 , 20 , 28 , 35 , 36 , 37 , 44 , 60 , 80 , 81 , 83 , 85 , 91 , 97 , 98 , 109 , 111 ]. BZDs were also the second most common drug detected in the merged database.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of them have been limited to either regional urban populations (Hammersley et al 1995;Jones et al 2002), particular types of drug death such as methadone related deaths (Fiddler et al 2001;Seymour et al 2003), or particular settings such as recent liberation from prison . One study examined DRDs across Scotland per 100 injecting drug users in 2000-2001 and found that older and male injecting drug users were at higher risk of dying of drug-related causes .…”
Section: Introductionmentioning
confidence: 99%